Inventory of Arthropods of Azorean Urban Gardens - Borges, Paulo A. V. (2022)
The data we present are part of the long-term project SLAM (Long Term Ecological Study of the Impacts of Climate Change in the natural forest of Azores) aiming to assess the impact of biodiversity erosion drivers on Azorean native biota, using long-term ecological data. Additionally to SLAM traps, nocturnal Active Aerial Searching and nocturnal Foliage Beating methods were used to sample, between 2017 and 2018, the arthropod biodiversity on two historical urban gardens of Azores, the “Jardim Botânico” of Faial Island, and “Jardim Duque da Terceira” of Terceira Island. This publication includes new data and updates the knowledge about the arthropod diversity and taxonomy of Arteaga et al. 2020, and contributes to the study of the urban gardens role to conservation of native biota.